2017
DOI: 10.5489/cuaj.4106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neutrophil-to-lymphocyte ratio on effects of targeted therapy for metastatic renal cell carcinoma patients with extrapulmonary metastasis

Abstract: Introduction: The aim of our present study was to investigate the impact of the pretreatment neutrophil-to-lymphocyte ratio (NLR) on the antitumour effects of targeted agents in patients with metastatic renal cell carcinoma (mRCC). Methods: The NLRs in 283 cases of molecular targeted therapy for mRCC were measured before starting the prescription of the molecular targeted agent. The significance of pretreatment NLR on the site of metastatic organs and on progression-free survival (PFS) in each case was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the molecular‐targeted therapy era, the IMDC risk classification is a standard risk‐based stratification . Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC . Recently, the CAR, a novel inflammation‐based prognostic score, has shown outstanding prognostic value in several cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the molecular‐targeted therapy era, the IMDC risk classification is a standard risk‐based stratification . Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC . Recently, the CAR, a novel inflammation‐based prognostic score, has shown outstanding prognostic value in several cancers .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC. [14][15][16] Recently, the CAR, a novel inflammation-based prognostic score, has shown outstanding prognostic value in several cancers. [17][18][19] However, only a few studies investigated the impact of CAR on prognosis in patients with mRCC, and no study compared the effect of CAR with the mGPS on prognosis in mRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes can show an antitumoral role through the induction of cytotoxic cell death [19][20], and perioperative lymphopenia was reported to be associated with inferior prognosis in patients with mRCC [21]. NLR is one of the most representative indexes that has been reported with its prognostic impact on mRCC [18][22] [23]. According to these reports, Tanaka et al [24] established an IMDC model modified using NLR.…”
Section: Discussionmentioning
confidence: 99%